Photodynamic therapy with methyl aminolevulinate in the treatment of basal cell carcinoma - A. A. Kubanov; I. N. Kondrakhina; N. V. Gribanov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article presents the results of the studies on the effectiveness of treatment basal cell carcinoma of the skin with photodynamic therapy with 5-aminolevulinic acid and methyl aminolevulinate. The results of the comparing trials between photodynamic therapy with methyl aminolevulinate and different other treatment modalities are presented.